Nest survival data confirm managed housing is an important component to the conservation of the eastern purple martin - Daniel Raleigh; James D. Ray; Blake A. Grisham; Joe Siegrist; Daniel U. Greene (Wildlife Society Bulletin)
ABSTRACT The purple martin (Progne subis) is entrenched in a consistent, long‐term decline. This is especially true for the subspecies east of the Rocky Mountains (P. s. subis), which today nests almost exclusively in provisioned housing (birdhouses and hollow gourds) provided by citizen scientists. One benefit of provisioned housing is reduced nest‐site competition with nonnative European starlings (Sturnus vulgaris) and house sparrows (Passer domesticus) when managed by citizen scientists. Increased competition for nest sites and subsequently lower productivity due to declining management of available housing is speculated to be primary factors for their long‐term declines. To assess whether managed housing promoted high nest‐survival metrics, we used a 19‐year database (1995–2013) of nest‐check records provided by Project MartinWatch, a citizen science program of the Purple Martin Conservation Association. We compared nest ecology metrics and survival among housing and entrance‐hole type to assess if specific provisioned housing or entrance‐hole type increased clutch size or number of chicks fledged. Using 72,627 nests across 8 regions monitored by citizen scientists, our major findings were 1) nest survival was >85% among 8 regions in the eastern United States and Canada; and 2) clutch size and number of fledglings produced were slightly larger in natural and artificial gourds with entrances designed to exclude European starlings; but 3) housing and entrance‐hole types were not important predictors of nest survival and clutch size had a small, inverse relationship with daily nest survival (βClutch = −0.002). Our results suggest managed housing is an important conservation tool based on previously undocumented high nest survival across the numerous artificial housing options. Our findings encourage the use of artificial and natural gourds with European starling‐resistant entrance holes, but promotion of managed artificial housing of any type in North America is beneficial and strongly encouraged. © 2019 The Wildlife Society.